The genetic mosaic. - Findlay, G (1993)
Blaschko's lines are the acknowledged markers which represent the patterns of systematized naevi. Their interpretation has remained mysterious, because certain special features which they exhibit are impossible to reconcile with any known anatomical system in the human body. It is proposed that by changing one's views on the nature and growth of the dermatome, the patterns of zoster, and the behaviour of tissue mosaicism, the major difficulties hitherto experienced will be overcome.